MM-wave backhauling for 5g small cells - Thair Al-Heety, Ahmed; Singh Jit Singh, Mandeep; Tariqul Islam, Mohammad; Hameed Ahmed, Ali (International Journal of Engineering and Technology, 2019)
The high capacity requirement for meeting the high demand of wireless application usage is the main issue in researches. Besides, to increase the capacity of the network, a new topology of cell configuration should be deployed which is the use of small cell configuration like micro and Pico cells with such configuration topologies in order to have high data rate network. This article aims to study the performance evaluation of the use of two 5G mm wave backhauling configurations. The first one is the star topology and the second one is the mesh topology. The main difference between them is the cooperation in mesh topology between cells to transfer data. The performance metric used in this project is the energy efficiency obtained from the two configurations when changing the frequency bands and path loss coefficient. The simulation results show that the changing the frequency bands in mesh configuration gives the same energy efficiency reached to 500 Mb/s at 15 nodes while the star configuration results reached less than 100 Mb/s at the same number of nodes. Â Â